Lateral Translation of the Patella in MPFC Reconstruction: A Biomechanical Study of Three Approaches - Cregar, William M.; Huddleston, Hailey P.; Shewman, Elizabeth F.; Cole, Brian J.; Yanke, Adam B. (The Journal of Knee Surgery, 2022)
The purpose of this study was to investigate whether differences exist in preventing lateral patellar translation between three distinct medial patellofemoral complex (MPFC) reconstruction procedures at varying knee flexion angles. Six cadaveric knee specimens were dissected, potted, and placed in a customized jig for testing. Lateral patellar displacement was measured at intervals between 0 and 90 degrees of knee flexion using a tensile testing machine with a 20 N lateral force applied to the patella. Each specimen was tested with the MPFC intact, sectioned, and after each of the three reconstruction techniques: MPFL, hybrid, and medial quadriceps-tendon femoral (MQTFL) reconstructions. There was significantly increased lateral patellar displacement following MPFC sectioning when compared with the intact state in early degrees of flexion (10–30 degrees) (p < 0.05). All three reconstruction groups restored patella stability and reduced lateral patellar displacement following sectioning from 0 to 30 degrees of flexion (p < 0.05). When compared with the intact group, all three reconstruction groups demonstrated reduced patella translation at full knee extension, while the MPFL and hybrid reconstruction groups additionally demonstrated significant reduction in patella translation at 10 degrees of flexion (p < 0.05). No significant differences were observed between the three reconstruction groups. This biomechanical study demonstrates the efficacy of three MPFC reconstruction techniques in patella stabilization following sectioning. Our results suggest that MPFL reconstruction may provide the most robust patella stabilization, whereas MQTFL reconstruction may be the most forgiving construct. This study suggests that MQTFL and hybrid reconstructions provide adequate resistance to lateral translation and may be used as an alternative to MPFL reconstruction.
Keywords: knee; medial patellofemoral complex; patellar instability